Acute Pericarditis and Pericardial Effusion in a Hypertensive COVID-19 Patient - Naqvi, Syeda Ghadeer Zehra (Cureus, 2020)
Coronavirus disease 2019 (COVID-19) is a contagious disease that has a potential of causing cardiovascular illness. Cardiac outcomes of COVID-19 mainly include acute coronary syndrome, heart failure, and left ventricular dysfunction. However, pericardial involvement is very rare. Here, we present a case of pericarditis and pericardial effusion in a known hypertensive COVID-19 patient. Our case was a diagnostic dilemma as the literature review mentioned that cardiovascular manifestations are mostly reported in symptomatic and critically ill patients of COVID-19. However, this patient has no viral respiratory illness, and is otherwise healthy.